(3YHK GdhdjO aj GdcdGe Ydi TYQ CHj YHGOI GdhdjO (B[ (3GdHMJQi (B]s - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s
(3ChdgG (B:s
(3KHJ eG ai OjhGf GdHMJQi eeG CUdM ef GdZdW GdPi hLO ai GdfSNI GdecJhH ai BNQgG CfgG HNW XaQ Hf YHO Gddg GdYLdi MQa GdgeRI ef GdJi RYe GdZQGH efHi GdCfHGA s
(3BNQgG (B:s
(3hcPdc GdbWYI GdJi ChdgG (B: (3SQi GdZeGe hYGOJfG ZhGOjg jLH Cf JKHJ ai MQa GdgGA CjVkG Je GdEedGA GdeYQha HYHK GdhdjO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3COH (B18) s
Keywords: (3GdCOHs